PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BRAND FASHION AIRLABELS DI SUMMARECON BEKASI MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING - Putri, Elna Rosdiana; Ali, Hapzi; Khan, Muhammad Asif; Sawitri, Ni Nyoman; Navanti, Dovina (SINERGI : Jurnal Riset Ilmiah, 2025)
The influence of promotion and product quality on purchasing decisions of the fashion brand Airlabels at Summarecon Mall Bekasi through purchase interest as an intervening variable. This study uses a quantitative method, with a sampling technique (Purposive Sampling), involving 119 respondents who have made purchases or at least have an interest in Air Labels products at Summarecon Bekasi. Data analysis was carried out using SmartPLS software, with Outer Model Test, Inner Model Test, and Hypothesis Test. The results of this study indicate that; 1) Promotion has a significant positive effect on Purchase Interest; 2) Product quality has a positive and significant effect on Purchase Interest; 3) Promotion has a positive effect on purchasing decisions; 4) Product quality has a positive effect on purchasing decisions; 5) Purchase interest has a positive effect on purchasing decisions; 6) Purchase interest is able to mediate Promotion on purchasing decisions; 7) Purchase interest is unable to mediate Product Quality on purchasing decisions.